Roll and yaw stabilisation using nonlinear energy method - Lim, Jen Nee Jones; Akmeliawati, Rini; Chee, Pin Tan (2007)
Automatic flight control systems have become increasingly vital ever since the emergence of airplanes. Automatic systems are not subject to fatigue and emotions as compared to the human pilot. As such, the possibility of human errors in flight control is minimized. Current automatic Flight Control Systems are designed based on classical control theories using linear controllers that are complex and inefficient. Since an aircraft is naturally nonlinear in its behavior, it is intuitive to design a nonlinear controller that could cover a wide variety of possible ‘extreme’ flight conditions. A novel controller utilizing the Nonlinear Energy Method was developed by Akmeliawati for the longitudinal dynamics of an aircraft, and has been proven to provide effective control and better performance when compared to an equivalent linear controller. The novel controller was designed using the Passivity-Based Control (PBC) technique. In this paper, a similar nonlinear controller was designed to direct the roll and yaw motion, which is part of the lateral dynamics of the aircraft. Simulations show that this PBC is able to stabilize both roll and yaw motion of the aircraft.